Prophetic Communication Praise on Instagram Social Media - Alifia Nabila; Ahmad Fahmi; Ayu Sri Wahyuni; Azhar Ubaidillah; Bilqis Nur Amalia; Ferdiansyah (Social Impact Journal, 2023)
Currently da'wah can be done through social media because it is easy to reach audiences in spreading Islamic teachings. The purpose of da'wah through social media is none other than to inspire each other and spread understanding about Islam through content. The purpose of this writing is to find out about prophetic communication through Instagram social media. The method used in this paper is qualitative, using content analysis through Instagram social media. The results of the discussion in this paper, in the last few decades, the number of social media users, especially Instagram, has increased. This allows preaching on social media to be efficient and affordable. Da'wah posts on Instagram usually contain content about beliefs (creeds), laws, morals, and ethics.